Analisis Wacana Islam Moderat: Kajian Tafsir Lisan Perspektif Gus Ahmad Bahauddin Nursalim - Tri Budi Prastyo; Hidayatul Fikra (Matan : Journal of Islam and Muslim Society, 2022)
The study of Islam in Indonesia are seen to be very diverse, both in terms of thoughts and procedures for carrying out worship. The term moderate Islam is now starting to be reinvigorated as a step to unite the religious understanding of the community. Differences in people's understanding are considered to be able to trigger the emergence of divisions that can damage the integrity of the Indonesia. This study aims to analyze moderate Islamic discourse in the study of oral interpretation of KH. Ahmad Bahauddin Nursalim broadcast via social media Youtube. This study used a qualitative approach through the descriptive-analytical method of Teun Van Dijk's Critical Discourse Analysis (AWK). The results indicated that moderate Islam in the study of oral interpretation from the perspective of KH. Ahmad Bahauddin Nursalim was different from Islamic view in the Middle East, although it has the same theological understanding. This understanding actually emphasizes that Islam is not a religion that carries hard currents, takes extreme actions by disbelievers or heretical. On the other hand, moderate Islam as Islam that is rahmatan lil 'alamin is in line with the teachings of Islam inherited by the Prophet Muhammad. This study concluded that moderate Islam is appropriate to use in this country of Indonesia which has a diversity of ethnicities, nations and religions.